The Relationship of Participation in Sports and Physical Activity to Body Objectification, Instrumentality, and Locus of Control Among Young Women - Parsons, Elizabeth M.; Betz, Nancy E. (Psychology of women quarterly, 2001)
The primary purposes of this study were to assess the possible relationship of sports participation during high school to body self-objectification, instrumentality and locus of control, and to explore the possibility that different sports might be differentially related to psychological variables according to the perceived stereotypical masculinity or femininity of the sport. Two studies were reported herein. In the first, using 195 male and female students, we examined perceptions of sports according to emphasis on physical appearance and perceived masculinity/femininity. These findings were used in Study 2, which included 437 college women, to describe sports participation along dimensions of both extent of participation and the nature of the sports in which the individual participated. Extent of participation in physical fitness activity was also assessed. Participation in sports and/or physical activity was associated with higher scores on the body shame subscale of McKinley and Hyde's (1996) Objectified Body Consciousness Scale, which indicates greater internalization of cultural standards of female beauty. Body shame was also related to participation in more “feminine” sports (those focusing more on female appearance). Physical activity was also consistently related to both instrumentality and locus of control. Further research is needed to understand the relationship of sports and physical exercise activities to body self-objectification and other indicators of psychological functioning among women.